2016
DOI: 10.14254/2071-8330.2016/9-2/13
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic determinants of permanent emigration from Romania. a Bayesian approach

Abstract: Abstract. Th e aim of this research is to identify some macroeconomic determinants for permanent emigration from Romania, in order to alleviate the negative consequences of this phenomenon in the origin country of the emigrates. For identifying the most relevant macroeconomic factors explaining the growth in the number of emigrants, the stochastic search variable selection was applied for various acceptance probabilities. Low increases in real earnings and the growth in poverty headcount ratio at $3.10 a day e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 13 publications
(12 reference statements)
2
21
0
Order By: Relevance
“…In countries that depend on remittances, these supported financial growth (the percentage of private credit or deposits in GDP), but also the private sector activity. As emigrants become permanent, the positive effects of remittances reduced (Simionescu, 2016). Moreover, Vogler and Rotte (1998) consider that trade liberalisation and greater openness to FDI can contribute to the development of these countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In countries that depend on remittances, these supported financial growth (the percentage of private credit or deposits in GDP), but also the private sector activity. As emigrants become permanent, the positive effects of remittances reduced (Simionescu, 2016). Moreover, Vogler and Rotte (1998) consider that trade liberalisation and greater openness to FDI can contribute to the development of these countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The empirical studies for Romania identified few determinants of emigration: poverty growth in Romanian regions, higher salaries and better social and economic environment in the destination countries compared to Romania, less risk of unemployment abroad, the perception of less corruption and better business opportunities in the destination countries, positive career expectations etc. (for example, De Sousa & Duval, 2010;Goschin & Roman, 2014;Roman, 2011;Simionescu, 2016). More than 70% of the Romanian people chose Italy and Spain as destination countries.…”
Section: Introductionmentioning
confidence: 99%
“…Interdisciplinary studies are scarce in front of Central and Eastern Europe (Simionescu, 2016), so we focused on that area, occasionally highlighting Hungarian features. According to our experience, Hungary is under-researched compared to Poland, which is regarded as its "fellow country".…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was already indicated above that ethnical background and cultural proximity do count, as countries attempt to lure back their fellows (Hungary-Romania). On the other hand, Simionescu (2016) found that between 1991 and 2014, Romanian people permanently left their home because of low earnings. It also bears some contradiction, since emigrating people are rarely coming from the poorest regions of Romania (Goschin et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation